REVIEW ON GREEN CHEMISTRY AND ITS APPLICATION - Kulshreshtha, Alka (International Journal of Research -GRANTHAALAYAH, 2015)
The chemical components in our environment are increasing day by day. Only some of them can be degraded but most of them are undegradable. These un degradable components create pollution. The addition of undegradable substances that causes instability, disorder, harm or discomfort to the ecosystem is termed as pollution. Pollution is creating a risk to the environment. Thus in order to reduce the risk of pollution a system should be introduced that must reduce the risk by not changing the effect but by changing the cause. Thus a concept named green chemistry was introduced.Green Chemistry or environmentally benign chemistry is the design of chemical products and processes that reduce or eliminate the use and generation of hazardous substances.